INDONESIAN DISCOURSE PARTICLES FOUND IN THE TRANSLATION OF ENGLISH YES/NO QUESTIONS IN THE RPG HONKAI: STAR RAIL - Raden Roro Shinta Felisia (International Journal Multidisciplinary Science, 2024)
In typical Indonesian dialogues or casual speech (cakap), particles are commonly used. The dynamics of the Role-Playing Game (RPG) Honkai: Star Rail are closely tied to character interactions, particularly through dialogues that include yes-no questions. This study aims to identify Indonesian discourse particles in the translation of English yes/no questions in the RPG Honkai: Star Rail. The researcher finds that there are thirteen (13) units or 69% of Indonesian discourse particles found in the translation of English yes/no questions. The discourse particles ya are the most frequent. This particle is 9 units, meanwhile, kan and dong are 3 units or 23% and 1 unit or 8% respectively. Since RPGs are a medium for delivering a variety of languages, it would be beneficial for other researchers to explore language use in RPGs further.